Growth responses of juvenile red swamp crayfish Procambarus clarkii Girard to several diets under controlled conditions - Fabião, António (2009)
The growth responses of juvenile crayfish, Procambarus clarkii to diets based on common fresh feedstuffs available from agriculture ans freshwater ecosystems were studied under controlled laboratory conditions. The dietary treatments were: fresh leaves and shoots of watercress, fresh potato tubers, fresh fish meat from mosquitofish and all the possible combinations of those ingredients on alternate feeding days. After 22 days, the results showed a significantly higher growth rate (P=0.05)in crayfish fed with mosquitofish meat.